Predictors of adolescent well-being during school closures: a systematic review and secondary analysis of REDS data from Slovenia - Veldin, Manja; Pertoci, Nina (Frontiers in Education, 2025)
IntroductionThe COVID-19 pandemic and prolonged school closures disrupted students’ daily lives, exacerbated existing challenges, and negatively impacted adolescent well-being.MethodsThis study identifies predictors of adolescent well-being during school closures by combining a systematic review of international research with a secondary analysis of data from a representative sample of Slovenian students (who experienced some of the longest school closures in Europe, resulting in a deterioration in well-being).ResultsThe findings suggest that adolescent well-being is the result of a dynamic interplay between individual, social, and environmental factors, with the relative influence of these factors varying between crisis and non-crisis contexts. Identified risk factors included, among others, female gender, low socioeconomic status, mental health difficulties, loneliness, disrupted daily routines, and elevated anxiety, whereas emotional regulation, adaptive coping, and perceived social support functioned as salient protective factors. Environmental stressors, including lockdown measures, home environment constraints, and exposure to infection, further exacerbated psychological distress. The Slovenian study demonstrates how national and cultural contexts can affect these results further, with some predictors, such as physical activity and anxiety, displaying mixed associations with well-being.DiscussionThese findings emphasise the need for context-sensitive, multi-level interventions that foster autonomy, competence, and connectedness to sustain adolescent well-being during stable periods and crises, and to inform future school and health policies.